CO Adsorption Properties of Activated Carbon Fibres under Ambient Conditions - Yoshitaka Nakahigashi; Hirofumi Kanoh; Tomonori Ohba; Masumi Baba; Yoshiyuki Hattori; Naoya Inoue; Masafumi Morimoto (Adsorption Science & Technology)
In this study, we investigated the possibilities of using activated carbon fibre (ACF) as a carbon capture and storage (CCS) technology. The CO 2 adsorption isotherms of ACFs with different porosities were systematically examined at 273 and 298 K under ambient pressure conditions. The porosities of the ACFs were characterized by the adsorption of nitrogen at 77 K. We analyzed the adsorption capabilities of three types of ACFs (A5, A10 and A20) having different slit-shaped pore widths, specific surface areas and micropore volumes. Our results reveal that A5 had ultramicropores and achieved a higher adsorption of CO 2 at low relative pressure (<0.015) at 273 K. However, A10, which had an average pore width of 0.9 nm, exhibited the highest adsorption capacity of 195 mg g −1 at a higher pressure of about 100 kPa, which is a relatively high value compared with that of conventional activated carbon. By establishing the temperature dependence of CO 2 adsorptivity and using Dubinin–Radushkevich analysis, we characterized the interaction energy between pores and CO 2 molecules. Our results shed light on the fundamental aspects of CO 2 adsorption of ACFs, moving them towards being a viable CCS.